SAT0739-HPR Occupational exposure to pesticides increases the risk of rheumatoid arthritis: results from the malaysian population-based case-control study. (12th June 2018) - Too, C.L.; Tan, L.K.; Nurul Aain, A.F.; Lau, I.S.; Nor Asiah, M.L.; Salsabil, S.; Heselynn, H.; Nor Shuhaila, S.; Wahinuddin, S.; Gun, S.C.; Eashwary, B.; Mohd Shahrir, M.S.; et al.
Abstract : Background: Several studies have suggested farming occupation with exposure to pesticides as risk factor for rheumatoid arthritis (RA). Objectives: We investigated the association between pesticides exposure and risk of RA subsets in the Malaysian population. Methods: Data from the Malaysian Epidemiological Investigation of Rheumatoid Arthritis (MyEIRA) population-based case-control study involving 1055 early RA cases and 1057 age, sex and residential area matched controls were analysed. All study subjects answered a structured questionnaire on a broad range of issues including occupational exposures to pesticides. The self-reported information on ever/never occupationally exposed to pesticides was used to estimate the risk of developing ACPA-positive and ACPA-negative RA. Association between pesticides exposure and the HLA-DRB1 shared epitope (SE) was evaluated. Results: The proportion of ACPA positivity in the RA patients was 64.4% and 1.9% in the normal controls. The presence of HLA-DRB1 SE alleles in RA patients was 40.2% and 15.8% in the normal controls. Our data demonstrated that occupational exposure to pesticides was significantly associated with an increased risk of developing RA in the Malaysian population (OR 2.31, 95% CI 1.12–4.73, p=0.03). The association between occupational exposure to pesticides and risk of RA was observed with ACPA-positive RA (OR 3.10 95% CI 1.49–6.47, p=0.003), but not with ACPA-negative RA. A dramatically increased risk for ACPA-positive RA was seen in individuals who both exposed to pesticides occupationally and carried SE alleles (OR 28.06, 95% CI 3.58–220.09, p<0.0001). Conclusions: This study demonstrates that occupational exposure to pesticides is associated with an increased risk of ACPA-positive RA in Malaysian population. References: [1] Sverdrup B, Källberg H, Bengtsson C, Lundberg I, Padyukov L, Alfredsson L, Klareskog L and the Epidemiological Investigation of Rheumatoid Arthritis study group. Association between occupational exposure to mineral oil and rheumatoid arthritis: results from the Swedish EIRA case–control study-Arthritis Research & Therapy2005;7:R1296-R1303. [2] Meyer A, Sandler DP, Beane Freeman LE, Hofmann JN, Parks CG. Pesticide Exposure and Risk of Rheumatoid Arthritis among Licensed Male Pesticide Applicators in the Agricultural Health Study. Environ Health Perspect2017;14;125(7):077010. Disclosure of Interest: None declared